Analyses of Meldonium (Mildronate) from blood, dried blood spots (DBS), and urine suggest drug incorporation into erythrocytes - Tretzel, L.; Görgens, C.; Geyer, H.; Thomas, A.; Dib, J.; Guddat, S.; Pop, V.; Schänzer, W.; Thevis, M. (International Journal of Sports Medicine, 2016)
Initially developed in the late 1970s for veterinary applications due to proposed growth-promoting effects in animals [5], meldonium has become an approved drug in selected Eastern European countries and is the subject of ongoing clinical trials focusing the compound`s anti-ischemic and cardioprotective properties [2] [3] [12] [15] as well as potential applications regarding diabetes, neurodegenerative disorders, and bronchopulmonary diseases. In the context of athletic performance, beneficial effects on the individuals` physical working capacity, increased endurance performance, and accelerated recovery after physical activity were discussed [4] [10] [11], mentioning oral doses of meldonium of up to 2.0?g per day over 2-3 weeks in the course of pre-competition preparation phases [4]. In 2015, the World Anti-Doping Agency (WADA) initiated a one-year monitoring program [22] regarding the prevalence of meldonium (mildronate) in doping controls. Obtained data demonstrated a considerable extent of meldonium use by athletes [8] [16], which was further corroborated by a significant number of declarations of use and analytical findings at the Baku 2015 European Games [18]. Subsequently, the WADA Prohibited List that became effective in January 2016 [24] classified meldonium as banned under S4 (Hormone and Metabolic Modulators).